Ultrasonic visualization technique for anatomical and functional analyses of the sciatic nerve in rats - Xu, Xiao-Dong; Lin, Lei; Qiu, Yu-Bei; Zeng, Bang-Wei; Chen, Ye; Liu, Jun-Le; Ye, Cai-Hong; Wang, Jia-Li; Liu, Pei-Chang; Zhang, Liang-Cheng (Frontiers in Neuroscience, 2023)
Ultrasound has been widely used in diagnosis and minimally invasive treatment of peripheral nerve diseases in clinical, but there is still a lack of feasibility analysis in rodent models of neurological disease. Herein, we systematically investigated the development law of sciatic nerve cross-sectional area of different genders with body weight through the ultrasound imaging anatomy of rat sciatic nerve, and the effectiveness and reliability of ultrasound-guided block around sciatic nerve in living rats were also explored. We first reported that the sciatic nerve cross-sectional area of rat was increased with age (F=89.17, P＜0.0001), males were higher than females (F=60.77, P＜0.0001), and there was positively correlated with body weight (r Male=0.8976, P<0.000, r Female=0.7733, P<0.0001). Behavioral observation of rats showed that the lower extremity complete block rate was 80% after the administration of drugs around sciatic nerve under ultrasound guidance, and staining with methylene blue occurred in all sciatic nerves and surrounding muscles and fascia of 20 ultrasound-guided injections. These results indicate that ultrasound visualization technology can be used as a new auxiliary evaluation and intervention therapy for animal models of peripheral nerve injury, and will supply overwhelming new references for the basic research of neurological diseases.